On Blaps Fabricius, 1775 (Coleoptera: Tenebrionidae) from Western Kazakhstan with description of a new species from Tyuleniy Archipelago (Caspian Sea) - Chigray, Ivan A.; Abdurakhmanov, Gayirbeg M.; Nabozhenko, Maxim; Shapovalov, Andrey M. (Zootaxa, 2016)
A new species of darkling beetles Blaps caspica sp. n. from Western Kazakhstan Kulaly Island (Tyuleniy Archipelago, Caspian Sea) is described. This new taxon belongs to the 6th group of the 2nd section according to Seidlitz’s classification and is most similar to Blaps kadyrbekovi G. Medvedev, 2004, B. lethifera Marsham, 1802 and B. parvicollis Zoubkoff, 1829. Blaps caspica sp. n. differs from B. kadyrbekovi by the presence of a hair tuft between male abdominal ventrites 1 and 2, from B. parvicollis by having narrow acute short spurs on the mesotibiae, the structure of the gastral spicula, ovipositor and female genital tubes, from B. lethifera by the slender elliptic body, punctated (not granulated) epipleura and the structure of the female genital tubes. Images, an identification key and local distribution are given for ten Western Kazakhstan species of the genus Blaps Fabricius, 1775.